ITALY 2023, RIFORMA CARTABIA INNOVATIONS IN THE CIVIL PROCESS AND ADR; POTENTIAL INTERAC-TIONS? - Matteucci, Giovanni (Revista Eletrônica de Direito Processual, 2023)
Civil cases pending in Italian civil courts at the end of 2019 no. 5,826,440. Delegated Law 69/2009 and Legislative Decree 28/2010 ruled mandatory civil commercial mediation in the contemporary Italian legal system. Strong opposition from lawyers and benign neglect from the judiciary. Main objection: “Mediation does not belong to the Italian legal culture”: History teaches the opposite! 2012, the intervention of the Constitutional Court, excess of delegation; back to voluntary mediation. Law decree 69/2013, called “Del fare”, ruled the OPT-OUT mandatory mediation procedure, the compulsory lawyer’s assistance and declared lawyers mediators “ope legis”! 2017, Alpa Commission (“A world of experience has opened up, that … until now had not been perceived in all its extent and complexity”); the final report remained in a drawer. Delegated Law 206/2011, Luiso Commission (“The process will be civil”), Legislative Decree 149/2022, Riforma Cartabia: major innovations in the code of civil procedure and ADR. The new cognitive process under ordinary procedure is based on the anticipation of the first hearing: documents by the parties already laid out, so that the judge, after the free and non-formal questioning of the parties, can proceed to assess the admissibility and relevance of the means of proof and set the trial-calendar. June 30, 2023, mediation 4.0 takes off: increase of compulsory subjects; enhancement of the court-mandated mediation, involvement of the public administration, regulation of the report of the technical consultant in mediation, ODR, opposition to injunctions, tax incentives and fines to achieve the effectiveness of the procedure. As of October 10, 2023, the standards for fees of procedures and quality of training are still pending. Will the requirements for the parties' lawyers to prepare all the necessary documentation immediately before the first hearing (and the associated expensive fees for their clients) induce the parties to consider going to mediation more in order to avoid litigation (and its costs)?